2021
DOI: 10.1016/j.joms.2020.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Odontogenic Infections: Disease Burden During COVID-19 at a Single Institution

Abstract: Purpose The purpose of this study was to document the effect of COVID-19 on patients presenting to University of Washington Oral and Maxillofacial Surgery (UW OMS) with an odontogenic infection. Materials and Methods The investigators designed a retrospective cohort study and enrolled a sample of 889 subjects who presented for an odontogenic infection from March 19 th to June 18 th in the years 2017, 2018, 2019, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 5 publications
1
13
1
Order By: Relevance
“…This didn't happen. A decrease in the accesses for odontogenic abscesses was also observed during lockdown in the United Kingdom [29,30], in the USA [31] and in France [32], but in our study, this decrease was also found in the post-lockdown period. It dropped from a percentage of 8.6% (prelockdown period) to 4.7% during the lockdown and then in the post-lockdown period to 6.7%.…”
Section: Discussionsupporting
confidence: 54%
“…This didn't happen. A decrease in the accesses for odontogenic abscesses was also observed during lockdown in the United Kingdom [29,30], in the USA [31] and in France [32], but in our study, this decrease was also found in the post-lockdown period. It dropped from a percentage of 8.6% (prelockdown period) to 4.7% during the lockdown and then in the post-lockdown period to 6.7%.…”
Section: Discussionsupporting
confidence: 54%
“…Johnson et al reported that a higher number of patients visited emergency endodontics clinics before the COVID-19 pandemic than during the pandemic (18). In our study, although there was a decrease in the number of individuals visiting undergraduate clinics of our endodontics department during the pandemic, the prevalence of individuals with the complaint of pain increased during the pandemic in comparison with the frequency before the pandemic (80.8% vs. 74%).…”
Section: Original Articlecontrasting
confidence: 62%
“…In contrast, a Swiss study showed an increase in daily case numbers during the lockdown periods, but only the pre-COVID period 2020 served as a reference [ 8 ]. Regarding the number of odontogenic infections, an American study by Johnson et al showed a numerical decrease over the limited period from March to June, but a proportional increase compared to the years 2017–2019 [ 12 ]. Overall, there is currently little epidemiological data on the use of dental emergency service in connection with the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%